Self-harm and suicidal behavior amongst adolescens in Iceland - Bergþóra Kristín Ingvarsdóttir 1989- (2018)
Adolescents’ self-harm and suicide attempts have become a major public health concern in many countries, and their prevalence is increasing among boys and girls. What most research on self-harm and suicide attempts has found is that those who self-harm have experienced some kind of a traumatic life event. The purpose of this study was to investigate the prevalence and gender difference for self-harm and suicidal behavior among adolescents in Iceland and to examine whether negative life events are a possible risk factor, using scores on a negative life events questionnaire (NLE). The data used in the study was pre-existing, collected by ISCRA in 2016. Participants were 6,098 adolescents from multiple secondary schools in Iceland, 3,022 boys and 2,979 girls. Results showed that 19.4% had self-harmed, 27.6% of them had seriously considered committing suicide, and 9.4% had tried to commit suicide. Those who scored highest on the NLE were significantly more likely to have self-harmed, seriously considered attempting suicide, or attempted suicide, than those who got no points on the questionnaire. Girls were also significantly more likely than boys to have ever self-harmed, considered committing a suicide, or attempted suicide. Keywords: Suicide attempts, self-harm, adolescents, NLE, gender differences Sjálfskaði og sjálfsvígstilraunir á meðal ungmenna er orðið að alvarlegu heilsufarsvandamáli í heiminum og tíðni þess er að aukast. Flestar rannsóknir sem hafa skoðað sjálfsskaða og sjálfsvígstilraunir ungmenna hafa sýnt fram á að ungmenni sem skaða sjálfan sig eða gera tilraunir til sjálfsvígs hafa gengið í gegnum einhvers konar áföll á ævinni. Tilgangur þessarar rannsóknar var að finna tíðni ungmenna á Íslandi sem höfðu skaðað sjálfa sig eða íhugað eða reynt sjálfsvíg, athuga mun á tíðni milli kynja og gá hvort að erfiðir atburðir eða áföll á lífsleiðinni væru hugsanlegur áhættuþáttur. Í rannsókninni voru notuð fyrirliggjandi gögn frá árinu 2016, sem Rannsóknir og greining söfnuðu. Þátttakendur voru 6098 ...